2015
DOI: 10.2174/1871523014666150407150533
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Polysaccharide Fraction of Curcuma longa Extract (NR-INF-02)

Abstract: The aim of the study was to investigate the safety and anti-inflammatory effects of polysaccharide fraction (F1) of Curcuma longa extract (NR-INF-02) in classical rodent models of inflammation. F1 was evaluated for its acute oral toxicity and found to be safe upto 5000 mg/kg body weight in rats. The anti-inflammatory activity of F1 was evaluated in acute (carrageenan - induced paw edema; xylene - induced ear edema) and chronic (cotton pellet - induced granuloma) models of inflammation. The results of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Bioactive polysaccharides derived from medicinal plants have gained many interests especially for biomedical applications due to their various pharmacological activities including wound healing stimulation [1], inhibition of cancer cell growth [2], modulation of immune responses [3], reduction of inflammation [4, 5] and inhibition of bacterial growth [6]. Several methods have been used to evaluate these bioactive phytocompounds with high sensitivity, resolution and quantitative detection such as high‐performance liquid chromatography [7], gas chromatography mass spectrometry [8] and Fourier transform infrared spectroscopy (FTIR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive polysaccharides derived from medicinal plants have gained many interests especially for biomedical applications due to their various pharmacological activities including wound healing stimulation [1], inhibition of cancer cell growth [2], modulation of immune responses [3], reduction of inflammation [4, 5] and inhibition of bacterial growth [6]. Several methods have been used to evaluate these bioactive phytocompounds with high sensitivity, resolution and quantitative detection such as high‐performance liquid chromatography [7], gas chromatography mass spectrometry [8] and Fourier transform infrared spectroscopy (FTIR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…2013[ 8 ] and Illuri et al . 2015[ 10 ] These two studies indicated that turmerosaccharides of NR-INF-02 contributed to the anti-inflammatory effects. The analgesic effect of turmerosaccharides rich fraction appears to be similar to the anti-nociceptive activity of synthetic drugs, tramadol that resulted in 55% of anti-nociceptive activity.…”
Section: Resultsmentioning
confidence: 99%
“…420. [ 10 ] Thus, these studies clearly indicated that the possible anti-inflammatory activity of NR-INF-02 is primarily due to turmerosaccharides. However, the turmerosaccharides rich fraction was not investigated in in vivo monosodium iodoacetate (MIA)-induced osteoarthritic (OA) pain model.…”
Section: Introductionmentioning
confidence: 90%
“…In the past decades, some bioactive polysaccharides have attracted much research attention owing to their wide range of biological activities, such as anti‐viral, anti‐inflammatory, antioxidant, anti‐ulcer, immunostimulatory, antitumor activity and so on . It is also worth mentioning that these natural polysaccharides have been recognized as a source of safe and potent natural medicine because of their lower toxicity and higher efficacy .…”
Section: Discussionmentioning
confidence: 99%